Same-visit HIV testing in Trinidad and Tobago - Ali Cameile; Musa David; Samiel Sheila; Duke Violet; Chang-Kit Catherine; Warner Cynthia (BMC, 2010)
Abstract Background The Ministry of Health (hereafter, Ministry) of Trinidad and Tobago is responsible for delivery of all health services in the country. The Ministry takes responsibility for direct delivery of care in the public sector and has initiated a process whereby those seeking HIV test results could obtain confidential reports during a single-visit to a testing location. The Ministry requested technical assistance with this process from the Caribbean Epidemiology Centre (CAREC). The United States Centers for Disease Control and Prevention (CDC) played an important role in this process through its partnership with CAREC. Methods Under the technical guidance of CAREC and CDC, the Ministry organized a technical working group which included representatives from key national HIV program services and technical assistance partners. This working group reviewed internationally-recognized best practices for HIV rapid testing and proposed a program that could be integrated into the national HIV programs of Trinidad and Tobago. The working group wrote a consensus protocol, defined certification criteria, prepared training materials and oversaw implementation of "same-visit" HIV testing at two pilot sites. Results A Ministry-of-Health-supported program of "same-visit" HIV testing has been established in Trinidad and Tobago. This program provides confidential testing that is independent of laboratory confirmation. The program allows clients who want to know their HIV status to obtain this information during a single-visit to a testing location. Testers who are certified to provide testing on behalf of the Ministry are also counselors. Non-laboratory personnel have been trained to provide HIV testing in non-laboratory locations. The program includes procedures to assure uniform quality of testing across multiple testing sites. Several procedural and training documents were developed during implementation of this program. This report contains links to those documents. Conclusions The Ministry of Health has implemented a program of "same-visit" HIV testing in Trinidad and Tobago. This program provides clients confidential HIV test reports during a single visit to a testing location. The program is staffed by non-laboratory personnel who are trained to provide both testing and counseling in decentralized (non-laboratory) settings. This approach may serve as a model for other small countries.